Efficacy of rice straw derived biochar for removal of Pb+2 and Zn+2 from aqueous: Adsorption, thermodynamic and cost analysis. (February 2022) - Sakhiya, Anil Kumar; Vijay, Virendra Kumar; Kaushal, Priyanka
Abstract: The conversion of rice straw to biochar through pyrolysis can produce a low-cost and efficient adsorbent that removes metal contaminants from the aqueous. Biochar was derived at various pyrolysis temperatures (300–500 °C) and analyzed the physicochemical properties. The physicochemical properties of biochar, including pH (8.23–10.25), surface area (12.78–64.56 m 2 /g), and surface morphology were enhanced at a higher temperature. Biochar produced at 500 °C indicated the highest adsorption of Pb +2 (17.93 mg g −1 ) and Zn +2 (25.73 mg g −1 ). The Pseudo-second order and Langmuir isotherm were the best fit for the experimental data. The negative value of Gibbs free energy signified that the sorption was thermodynamically viable and of a spontaneous process. The cation exchange played a major role in adsorption, contributing to about 60 and 70% of total Pb +2 and Zn +2 adsorption. Cost assessment of biochar production validated its cost viability compared to commercially accessible adsorbents. Graphical abstract: Unlabelled Image Highlights: Slow pyrolysis of rice straw has been carried out at different temperatures. Physiochemical and surface properties of biochar enhanced at a higher temperature. Bio-oil contains a high amount of phenolic compounds and yield at 500 °C. The gas heating value and carbon conversion are enhanced by increasing temperature. The energy and exergy efficiency of process was improved at a higher temperature.